An idealized self or the real me? Predicting attraction to online dating profiles using selective self-presentation and warranting. Issue 3 (2nd July 2016) - Wotipka, Crystal D.; High, Andrew C.
ABSTRACT: Online daters construct their profiles to attract potential partners and viewers' assessments are based on the content of dating profiles. However, little is known about the mechanisms or nature of the associations that connect variations in profile content to outcomes. This study examined the presence of selective self-presentation (SSP) and warranting content as predictors of viewers' impressions and intentions to act on dating profiles. A national sample of online daters ( N = 316) provided their impressions and intended outcomes after viewing manipulated dating profiles. Results indicate that high levels of SSP decrease intentions to act on a dating profile because users find these profiles to be less socially attractive, whereas profiles with high warranting value increase positive outcomes by eliciting trust.